2017
DOI: 10.12691/jmdv-5-1-4
|View full text |Cite
|
Sign up to set email alerts
|

Performance Mapping of an Aluminum - Nitinol Composite Vibrating Beam

Abstract: Dynamic control of a vibrating beam is critical to the efforts of mitigation of high cycle fatigue, as it is a leading cause of component or engine failure. Recent advances in composite structures have afford the ability to control the eigenvalue, eigenvectors, and amplitude of vibration through the use of the shape memory effect of shape memory alloys (e.g. Nitinol). These "smart materials" are proven to create active damping and variable stiffness in engine components is an innovative concept. Research prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…An experimental study by Nakshatharan [24] using SMA wire applied externally to a clamped-free beam with a constant excitation frequency confirmed that beam tip amplitude reduction of approximately 60% can be achieved in first bending mode. The introduction of the shape memory effect, whereby the shape memory alloy material acts as both a damper and a means of variable stiffness have been confirmed for HCF mitigation [16,17,18,19] using thin sheet metal SMA topically adhered onto a clamped-free beam. This study highlights an amplitude reduction of 92% in the second bending mode with constant excitation frequency.…”
Section: Sma Vibration Controlmentioning
confidence: 92%
“…An experimental study by Nakshatharan [24] using SMA wire applied externally to a clamped-free beam with a constant excitation frequency confirmed that beam tip amplitude reduction of approximately 60% can be achieved in first bending mode. The introduction of the shape memory effect, whereby the shape memory alloy material acts as both a damper and a means of variable stiffness have been confirmed for HCF mitigation [16,17,18,19] using thin sheet metal SMA topically adhered onto a clamped-free beam. This study highlights an amplitude reduction of 92% in the second bending mode with constant excitation frequency.…”
Section: Sma Vibration Controlmentioning
confidence: 92%